2004
DOI: 10.1590/s0100-40422004000200008
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-trace monitoring of copper in environmental and biological samples by inductively coupled plasma atomic emission spectrometry after separation and preconcentration by using octadecyl silica membrane disks modified by a new schiff's base

Abstract: Recebido em 26/2/03; aceito em 24/10/03 Ultra-trace amounts of Cu(II) were separated and preconcentrated by solid phase extraction on octadecyl-bonded silica membrane disks modified with a new Schiff , s base ( Bis-(2-Hydroxyacetophenone) -2,2-dimethyl-1,3-propanediimine) (SBTD) followed by elution and inductively coupled plasma atomic emission spectrometric detection. The method was applied as a separation and detection method for copper(II) in environmental and biological samples. Extraction efficiency and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The detection limit of membrane sensor presented in Table 2 is in good agreement with the dielectric constants of solvent mediator. 2.4x10 -6 3.2x10 -5 3.8x10 -5 1.1x10 -8 1.1x10 -8 1.2x10 -8 The presence of lipophilic anions in the composition of cationic-selective membrane microelectrodes, not only diminishes the ohmic resistance and enhances the potential behavior and selectivity, but also in poor extraction capacities, increases the sensitivity of the membrane electrodes, has long been known 22 . After various experiments it was observed that the presence of 1% NaTPB as membrane component significantly increases the sensitivity of membrane electrode.…”
Section: Optimization Of Membrane Componentsmentioning
confidence: 99%
“…The detection limit of membrane sensor presented in Table 2 is in good agreement with the dielectric constants of solvent mediator. 2.4x10 -6 3.2x10 -5 3.8x10 -5 1.1x10 -8 1.1x10 -8 1.2x10 -8 The presence of lipophilic anions in the composition of cationic-selective membrane microelectrodes, not only diminishes the ohmic resistance and enhances the potential behavior and selectivity, but also in poor extraction capacities, increases the sensitivity of the membrane electrodes, has long been known 22 . After various experiments it was observed that the presence of 1% NaTPB as membrane component significantly increases the sensitivity of membrane electrode.…”
Section: Optimization Of Membrane Componentsmentioning
confidence: 99%
“…8,9 Because of these problems, a separation and preconcentration process is necessary for improving the sensitivity of the analytical detection method and for providing low detection limits. Various separation/preconcentration techniques, including solid phase extraction (SPE), 10,11 ion exchange, 12 cloud point extraction, 13 membrane filtration, 14 electroanalytical techniques, 15 and coprecipitation, 16 are used prior to instrumental determination of trace elements. SPE is the most widely used preconcentration technique for the determination of trace elements.…”
Section: Introductionmentioning
confidence: 99%
“…Various SPE materials have been used for the preconcentration of trace metal ions as their chelates, activated carbon (Ensafi and Ghaderi 2008;Tsogas et al 2009), polyurethane foam (Anthemidis et al 2003), Chromosorb 105 (Buke et al 2009), Ambersorb-572 (Baytak and Türker 2006), modified silicas, and C18 disks (Mashhadizadeh et al 2008;Shemirani et al 2004;Mohammadhosseini and Tehrani 2006;Ganjali et al 2004;Shamsipur et al 2000;Kim et al 2006); cotton (Faraji et al 2009), surfactant-coated alumina (Dadfarnia et al 2005;Absalan and Goudi 2004), etc. have been successfully used as solid phase extraction materials for the preconcentration of trace elements.…”
Section: Introductionmentioning
confidence: 99%